Sketches of landscapes : philosophy by example - Stroll, Avrum, 1921-2013 (MIT Press, 1998)
"Avrum Stroll accepts the ancient tradition that one of the tasks of philosophy is to give an accurate account of the world's features, both animate and inanimate. But, he contends, because these features are inexhaustibly complex, no single theory or conceptual model can provide a complete account. Stroll's approach is piecemeal and example-oriented. In stressing the importance of examples, his work runs counter to one of the most powerful and seductive ways of thinking about the world - the Platonic tradition, which denigrates examples in the search for essences. Stroll favors pluralism, on the ground that this is how the world is."--Jacket